Impact resistance efficiency of bio-inspired sandwich beam with different arched core materials - Ahmad B. H., Kueh; Chun Yean, Tan; Mohd Yazid, Yahya; Mat Uzir, Wahit (Techno-Press, 2022)
Impact resistance efficiency of the newly designed sandwich beam with a laterally arched core as bio inspired by the woodpecker is numerically investigated. The principal components of the beam comprise a dual core system sandwiched by the top and bottom laminated CFRP skins. Different materials, including hot melt adhesive, high density polyethylene (HDPE), acrylonitrile butadiene styrene (ABS), epoxy resin (EPON862), aluminum (Al6061), and mild carbon steel (AISI1018), are considered for the side arched core layer of the beam for impact efficiency assessment. The aluminum honeycomb takes the role of the second core. Contact force, stress, damage formation, and impact energy for beams equipped with different materials are examined. A diversity in performance superiority is noticed in each of these indicators for different core materials. Therefore, for overall performance appraisal, the impact resistance efficiency index, which covers several chief impact performance parameters, of each sandwich beam is computed and compared. The impact resistance efficiency index of the structure equipped with the AISI1018 core is found to be the highest, about 3 10 times greater than other specimens, thus demonstrating its efficacy as the optimal material for the bio inspired dual core sandwich beam system.